Systematic review and meta-analysis of the relationships between real-time neurofeedback training parameters and acquisition of neural modulation - Galang, Eldrick V.; Velásquez, Miguel A.; Elcin, Dehan; O'Connell, Samantha; Wieck, Julian; McNair, Savannah; Colombo, Paul J. (Frontiers in Human Neuroscience, 2025)
IntroductionReal-time neurofeedback is an emerging method for regional modulation of neural activity with physiological and behavioral effects that persist beyond the duration of feedback sessions. However, many individuals fail to achieve successful modulation, a challenge known as the “neurofeedback inefficacy problem.” This study examined how methodological parameters of neurofeedback training influence the acquisition and retention of neural modulation in healthy adults.MethodsA systematic search identified eligible studies, resulting in 55 participant groups included in the meta-analysis. Standardized mean differences (Hedges' g) were calculated for changes in neural activity from first to last session and from pre- to post-training. Subgroup analyses and meta-regression were conducted to assess the impact of discrete and continuous moderators.ResultsThis meta-analysis identified four parameters associated with significant neural modulation in the desired direction: the neurofeedback imaging device used, complexity of the feedback stimulus, presence of a pre-training rehearsal trial, and EEG target oscillations.DiscussionThis meta-analysis highlights key methodological factors that shape neurofeedback efficacy in non-clinical populations. Findings may serve to better understand how methodological variables used in neurofeedback influence the acquisition and retention of neural modulation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022357160, identifier: CRD42022357160.